Irrigation with saline-sodic water: effects on two clay soils - Giovanna Cucci; Giovanni Lacolla (Italian Journal of Agronomy, 2013)
The results of a 4-year experiment aimed at evaluating the effect of irrigation with saline-sodic water on the soil are reported. The research was carried out at the Campus of the Agricultural Faculty of Bari University (Italy) on 2 clay soils (Bologna – T1 and Locorotondo – T2). The soils were cropped to borlotto bean (Phaseolus vulgaris L.), capsicum (Capsicum annuum L.), sunflower (Helianthus annuus L.), wheat (Triticum durum Desf) grown in succession; the crops were irrigated with 9 saline-sodic types of water and subjected to two different leaching fractions (10% and 20% of the watering volume). The 9 solutions were obtained dissolving in de-ionised water weighted amounts of sodium chloride (NaCl) and calcium chloride (CaCl2), deriving from the combination of 3 saline concentrations and 3 sodicity levels. The crops were irrigated whenever the water lost by evapotranspiration from the soil contained in the pots was equal to 30% of the soil maximum available water. The results showed that, though the soils were leached during the watering period, they showed a high salt accumulation. Consequently, the saturated soil extract electrical conductivity increased from initial values of 0.65 and 0.68 dS m-1 to 11.24 and 13.61 dS m-1 at the end of the experiment, for the soils T1 and T2, respectively. The saline concentration increase in irrigation water caused in both soils a progressive increase in exchangeable sodium, and a decrease in exchangeable calcium and non-significant variations in exchangeable potassium (K) and magnesium (Mg).